2011
DOI: 10.1002/app.33534
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of alkali‐soluble photosensitive polysiloxane urethane acrylate

Abstract: A novel alkali-soluble photosensitive polysiloxane urethane acrylate (APSUA) was synthesized via reacting bifunctional isocyanate with three kinds of hydroxyl group respectively, from hydroxyl silicone oil, dimethylol propionic acid (DMPA), and a compound which also has acrylate groups. The compound was prepared via reacting acrylic acid with N,N,N 0 ,N 0 -tetraglycidyl -4,4 0 -diamino diphenyl methane (AG-80). The optimum temperature for the synthesis reaction of APSUA was found to be 50 C. The structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Hyperbranched polyester (HBPET) is a kind of polymer with branched chains and multifunctional groups, which can be used as a polymer plasticizer . In addition, HBPET has better compatibility with resins or starch and resistance to migration in a polymer matrix than small polar molecules . Our group found that hyperbranched poly(citrate glyceride) not only had good plasticizing effect and resistance to migration in starch, but also could inhibit the moisture absorption of starch …”
Section: Introductionmentioning
confidence: 98%
“…Hyperbranched polyester (HBPET) is a kind of polymer with branched chains and multifunctional groups, which can be used as a polymer plasticizer . In addition, HBPET has better compatibility with resins or starch and resistance to migration in a polymer matrix than small polar molecules . Our group found that hyperbranched poly(citrate glyceride) not only had good plasticizing effect and resistance to migration in starch, but also could inhibit the moisture absorption of starch …”
Section: Introductionmentioning
confidence: 98%
“…Therefore, hyperbranched polyesters are widely used in coatings, polymer blending modification, biological materials, and drug carriers . For plasticization, the properties of hyperbranched polyesters, such as their larger molecular weights, high number of branches, and more multifunctional groups, make their compatibility with host polymers and resistance to migration better than those of linear and small plasticizers . Additionally, hyperbranched polyesters can be synthesized by a simple one‐pot method that can be tailored by changing the recipes or procedures to meet certain requirements.…”
Section: Introductionmentioning
confidence: 99%
“…AHBPSUA with these properties has potential application in solder resist ink. 16 The molecular structure of HBPÀOH was shown in Scheme 1. The degree of branching of HB 1 PÀOH, HB 2 PÀOH, and HB 3 PÀOH is 6, 12, and 24, respectively.…”
Section: Introductionmentioning
confidence: 99%